REPRESENTASI TOLERANSI ANTARUMAT BERAGAMA DALAM FILM “JANGAN PANGGIL MAMA KAFIR” - Nisrina Audya Alexandra G.; Syifa Aulia; Naila Azizah (PT. Saha Kreasi Indonesia, 2026)
Film is one form of mass communication media that has a function not only as entertainment but also as a means of delivering social, cultural, educational, and moral messages to society. Through its storyline and characters, films can depict the reality of life occurring in social environments. One Indonesian film that addresses family life issues is